2022
DOI: 10.3389/fpls.2022.872950
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Wood-Anatomical Features and Resistance Drilling Density in Norway Spruce and European Beech

Abstract: Environmental conditions affect tree-ring width (TRW), wood structure, and, consequently, wood density, which is one of the main wood quality indicators. Although studies on inter- and intra-annual variability in tree-ring features or density exist, studies demonstrating a clear link between wood structure on a cellular level and its effect on wood density on a macroscopic level are rare. Norway spruce with its simple coniferous structure and European beech, a diffuse-porous angiosperm species were selected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…However, it is essential to exercise caution when applying these findings, as variations may be species-specific, owing to differences between hardwood and softwood's internal structures. Additional testing is necessary to ensure broader applicability, taking into consideration factors such as wood anatomy [54] and variations in spiral grain [55], and also greater replication within each species. In particular, hardwoods may require further research to fully understand the relationships between basic density and the parameters "a" and "b", due to their more complex internal structures.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is essential to exercise caution when applying these findings, as variations may be species-specific, owing to differences between hardwood and softwood's internal structures. Additional testing is necessary to ensure broader applicability, taking into consideration factors such as wood anatomy [54] and variations in spiral grain [55], and also greater replication within each species. In particular, hardwoods may require further research to fully understand the relationships between basic density and the parameters "a" and "b", due to their more complex internal structures.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Nikolas et al 2020 found that the drilling resistance technique can be useful for assessing silvicultural, genetics, and ecological studies of forest trees. Not only wood density, and other wood properties can also be explored through NDT drilling resistance techniques, such as the anatomical characteristics of grain direction and features of wood (Sharapov et al 2021;Arnič et al 2022). In addition, this technique has reportedly been used to estimate the age of pine, oak, and birch trees (Szewczyk et al 2018), but it was reported that drilling resistance density technique should not be used to replace dendrochronology in climate-tree growth studies (Orozco-Aguilar et al 2018).…”
Section: Modeling Of Wood Basic Density Using the Resistographmentioning
confidence: 99%